(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Functional analytic psychotherapy has a long history in Brazil. Nevertheless, its theoretical foundations are sometimes misunderstood. Different models intertwine in its literature. One is based on five general rules that can, in principle, also be applied in other behavioral therapies. A second one consists of a 12-point protocol that describes the therapist’s behavior step by step as a distinct procedure from other behavioral approaches. According to the third model, awareness, courage, and love are the active ingredients of the treatment. While the first model shares a close family resemblance with Brazilian behavior analytic therapy in its radical behavioral foundation, the second model has a more technical slant, tending toward more topographical definitions of therapeutic strategies, and the third model involves an experiential logic shared with acceptance and commitment therapy and dialectical behavior therapy amongst other third wave treatments. The present text discusses some implications of this plurality of clinical visions.